A degradation model of mode-I fracture toughness of rock under freeze-thaw cycles. (October 2021) - Deng, Zhengding; Zhan, Xingxin; Zeng, Wei; Yang, Shikou; Wu, Jianqi
Highlights: A calculation model of rock tensile strength that can reflect the degradation of freeze–thaw cycles is established. A calculation model of mode-I fracture toughness under freeze–thaw cycles is established. The influence of sensitive parameters on mode-I fracture toughness is discussed. Abstract: The mode-I fracture toughness of rock is one of the key mechanical indexes to measure the resistance of rock to its own crack propagation. The mode-I fracture toughness of rock mass in cold region is normally deteriorated by freeze–thaw cycle under temperature variation. Based on the theory of pore expansion, the meso -deterioration mechanism of pores in rock under the action of ice frost heave is analyzed, and the meso -deterioration model of tensile strength is formulated. The evolution equation of mode-I toughness is built according to the relationship between the mode-I fracture toughness and the tensile strength. The predicting model is validated by comparing with actual test. The results show that the falling of freezing temperature imposed a significant effect on the mode-I fracture toughness when the freezing temperature is above −10 °C. The migration of pore water decreases when the freezing time is between 2 h and 8 h, which leads to the sensitivity of fracture toughness to freezing time. The deterioration range of mode-I fracture toughness decreases gradually when the debris loss ratio is lower than 0.9. The control of debris loss is essential for the long-term stability of rock mass engineering in cold regions.